Banks' Financial Reporting Frequency and Asset Quality - Balakrishnan, Karthik; Ertan, Aytekin (The Accounting Review, 2018)
ABSTRACT We examine the effects of banks' financial reporting frequency from 2000 to 2014 and find that quarterly reporting improves their loan portfolio quality. Sample banks experience a relative decrease of about 11 percent in their nonperforming loans after switching to quarterly financial disclosures. Consistent with market discipline enhancing lending practices, these results are stronger in regimes with weaker depositor insurance and external monitoring, and in those with stronger capital markets. We also find that banks that provide quarterly financial information experience lower deposit interest rates and credit default swap spreads. Collectively, our findings suggest that quarterly reporting reduces banks' risk-taking. JEL Classifications: G21; G28; G32; M41; M48.